2022
DOI: 10.3390/w14091414
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Water Quality of Buritis Lake

Abstract: The implementation of natural parks in cities is a current and controversial theme. Therefore, in Lake Buritis, which is a leisure area for the population of the city of Goiatuba, Goiás, Brazil, the quality of the water was analyzed, carrying out quantitative tests of the water samples at six different points between the source and the outlet of the lake that flows into the stream, Chico À Toa. Physical–chemical tests (turbidity, pH, alkalinity, electrical conductivity, color, nitrate and hardness parameters),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 65 publications
1
2
0
Order By: Relevance
“…Nitrate is among the parameters that contributed to the decrease in the indices (Table 3; Figure 4). A similar finding is also reported by Kikuda et al [41], who studied Buritis Lake (Brazil). Even a slight decrease in nitrogen contents in Lake Union improves lake trophic status, but adding nutrients to the lake promotes eutrophication.…”
Section: Resultssupporting
confidence: 90%
“…Nitrate is among the parameters that contributed to the decrease in the indices (Table 3; Figure 4). A similar finding is also reported by Kikuda et al [41], who studied Buritis Lake (Brazil). Even a slight decrease in nitrogen contents in Lake Union improves lake trophic status, but adding nutrients to the lake promotes eutrophication.…”
Section: Resultssupporting
confidence: 90%
“…Likewise, Macar et al 36 determined that Co(NO 3 ) 2 stress reduced MI and showed a cytotoxic effect in A. cepa . Kikuda et al 37 reported significant changes in MI rates of A. cepa germinated with lithium-containing Buritis Lake water.
Figure 3 Effects of Li 2 CO 3 application on dividing cell number and MI in meristematic cells.
…”
Section: Resultsmentioning
confidence: 99%
“…Liu et al 39 showed that different metal ions can cause varying degrees of nucleus, nucleolus and chromosome irregularities in A. cepa . It has been reported in the literature that DNA integrity changes and chromosomal damage occur in A. cepa germinating with water samples containing lithium 37 .…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, in many areas around the world, the transport of pollutants through the vertical connectivity between surface water and aquifers as a consequence of human activities has become a critical issue. This is due to the increase in population, industry, agriculture, and livestock [1][2][3]. Indeed, some phenomena serve as continuous warnings about the deterioration resulting from the improper use of water and other natural resources, although certain issues may necessitate more in-depth investigation for their detection.…”
Section: Introductionmentioning
confidence: 99%